PENGARUH PEMAHAMAN HAK ASASI MANUSIA (HAM) TERHADAP SIKAP MENGHARGAI PENDAPAT ORANG LAIN PADA MAHASISWA PROGRAM STUDI PPKN FKIP UAD - Susilawati, Wiwik Okta; Novitasari, Ana; Prananda, Gingga; Apreasta, Lika; ., Andiyanto (Inspiratif Pendidikan, 2020)
The formulation of the problem in this study is is there a meaning of understanding human rights towards other people's opinions? The purpose of this research is to see whether or not there is an understanding of human rights regarding the attitudes of other people's opinions. The research was conducted with a quantitative approach. The research sample consisted of 55 students of the PPKn FKIP UAD class of 2009-2014 who had taken the Human Rights and Democracy Education courses. The data was collected through a multiple choice test (multiple choice) to measure the variable understanding of human rights and a questionnaire to measure the variable of respect for other people's opinions. The data analysis method used was product display analysis and simple regression analysis. The results showed that Ho was rejected and Ha was accepted or stated that "there is an effect of understanding human rights on respect for others" based on the calculation of the coefficient of determination calculated as 8.4%. This indicates that as much as 8.4% of changes in the attitude of respecting others who respect human rights.